Nałkowska i Komornicka, czyli kto zawinił - Helbig-Mischewski, Brygida (My University, 2013)
The author analyses the love-hate relationship between Zofia Nałkowska and her seven years’ senior, the legendary painter Maria Komornicka, who was for a time romantically ivolved with Zofia’s father — Wacław Nałkowski — and her friend — Cezary Jellenta. The relationship between the two writers has excited emotional reponses from researchers for many years. Two critics specializing in Komornicka have shown their interest most explicitly: Izabela Filipiak and Edward Boniecki. They accuse Nałkowska of not maginalizing Komornicka’s role in women’s literature of early 20th century, of unfeeling attitude for Komornicka’s tragic fate, even though Nałkowska was inspired by her in the early age, and of the failure to help Komornicka, when she was declared insane and disempowered after her symbolic transformation into a man. Researchers have so far seen Komornicka as a lost and harmed person, whereas Nałkowska was perceived as the morally questionable winner. However, Hanna Kirchner, who specializes in Nałkowska, has recently shown interesting sources of Nałkowska’s dislike for Komornicka, pointing out to a forgotten juvenile poem called "Historia „Forpoczt”". The author of the article, who also wrote a monograph about Maria Komornicka, analyses the arguments presented by critics of both writers, observing the relation between Nałkowska and Komornicka from a neutral ground, without sharing the dynamic of hasty accusations.
Nałkowska and Komornicka, or: Whose Fault It Was
Keywords: Nałkowska and Komornicka; rivarly between writers; feminist interpretation of author’s biography; relations between Young Poland women authors; functions of patriarchal mentors; Wacław Nałkowski; Cezary Jellenta